Biology and life cycle of Euploea netscheri Snellen, 1889 (Lepidoptera: Danainae) on Hoya host plants (Apocynaceae) - Daawia Daawia; I Made Budi; Bambang Suhartawan (Jurnal Biologi Papua, 2026)
Biological observations and life cycle studies of Euploea netscheri Snellen, 1899 on Hoya species were conducted at Yadikap Garden, Arso 2, Keerom, Papua, Indonesia, from June to August 2024.  Eggs laid by female butterflies on Hoya leaves were observed to record hatching time and the duration of the egg stage. Additionally, the total number of larval instars, the duration of each instar, and the duration of the pupal stage until emergence of the imago were documented. Measurements of the length of eggs, larvae, pupae, and adult butterflies were carried out using a caliper. The behavior and morphological characteristics of each larval instar, as well as those of the pupae and adults, were observed and recorded. Female E. netscheri butterflies were found to lay eggs on the leaves of Hoya globulifera and H. pachiphylla. The species completed its life cycle in approximately 22–25 days, consisting of an egg stage of about 3 days, a larval stage of 12–14 days, a pre-pupal stage of 1 day, and a pupal stage lasting 6–7 days. The results of this study provide the first record of the distribution, biology, and life cycle of E. netscheri in Keerom, Papua. New information is also presented regarding its larval host plants, namely H. globulifera and H. pachiphylla.